2016
DOI: 10.1002/jsfa.7811
|View full text |Cite
|
Sign up to set email alerts
|

A combination of additives can synergically decrease acrylamide content in gingerbread without compromising sensory quality

Abstract: The present study demonstrates that the combination of additives NaHCO /Ca /citric acid synergically decreases AA content in gingerbread without compromising the sensory quality. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Thus, higher thermal input explains, on the one hand, a higher acrylamide content and, on the other hand, a darker surface of the product (i.e., lower L*-value). We observed a similar relationship between acrylamide content in gingerbread and the L*-value (r = −0.49) in our previous experiment [ 58 ].…”
Section: Discussionsupporting
confidence: 83%
“…Thus, higher thermal input explains, on the one hand, a higher acrylamide content and, on the other hand, a darker surface of the product (i.e., lower L*-value). We observed a similar relationship between acrylamide content in gingerbread and the L*-value (r = −0.49) in our previous experiment [ 58 ].…”
Section: Discussionsupporting
confidence: 83%
“…This result indicates that, besides dihydromyricetin, the other polyphenols contained in vine tea extract also contributed to the inhibition of acrylamide formation during bread baking. Komprda et al [31] reported that the synergism of components (NaHCO 3 /Ca 2+ /citric acid) leads to a possible decrease of acrylamide in gingerbread. However, whether these polyphenols in vine tea extract interact with each other in inhibiting the formation of acrylamide in the present study, such as synergism or antagonism, needs to be further confirmed.…”
Section: Quantification Of Acrylamide With Lc-msmentioning
confidence: 99%
“…It can be produced in different forms, such as plain or opalescent, co-extruded, or coated on both sides with acrylic. The acrylic coating is often used in combination with polyvinyl chloride (PVC)/polyvinylidene chloride (PVDC) copolymer because it provides a higher barrier for oxygen but also provides a stronger barrier effect for taste and aroma compared to conventional polypropylene (Robertson, 1994;Galić et al, 2009;Komprda et al, 2017).…”
Section: Introductionmentioning
confidence: 99%